Patient Experience of Quality on Diabetes Mellitus Care in Primary Health Care: Integrative Literature Review - La Ode Nuh Salam; Suni Hariati; Saldy Yusuf; Sitti Nurhadijah (Journal La Medihealtico, 2025)
This review aims to summarize the evidence from previous studies on patients' experiences of quality diabetes mellitus care in primary healthcare. Methods: Referring to Whittemore & Knafl's methodology for integrative literature review by searching articles in six databases namely: PubMed, CINAHL, EBSCOhost, ProQuest, ScienceDirect, Garuda; Google Scholar search engine; and one publisher website (Wiley Online Library) between 2017-2022. Inclusion criteria included: original articles, samples of DM patients aged >18 years, from all countries with English and Indonesian text. Results: Data were analyses by assessing the similarity of results between studies, then synthesized using narrative analysis. Seven studies met the inclusion criteria, five of which reported patients' experiences of low-quality DM care in primary healthcare due to inadequate structures, suboptimal care processes and clinical outcomes. Only two studies reported experiences of high-quality DM care due to adequate equipment, schedule organization, care coordination and good doctor-patient interaction.Conclusions: Patients' experiences of low-quality DM care in primary healthcare were attributed to inadequate structures, suboptimal care processes and poor clinical outcomes, whereas high quality DM care was associated with adequate equipment, good scheduling, care coordination and good doctor-patient interactions.